Diagnóstico de la calidad de suelo en zonas degradadas del parque nacional Antisana, determinando la mejor tegnología de remediación disponible, en el periodo 2021-2022. - Salazar Ligña, Ana Gabriela (2022)
This research was carried out in the Antisana National Park in the San Simón sector at an altitude of 4178-4217 m.a.s.l., This area has been characterized in the past by overgrazing activities used as roosting grounds for grazing cattle. This activity decreases biodiversity and biomass due to the trampling of the animals, especially because of their weight; This is the problem for the regeneration and natural growth of the grasslands and plants of the place, which is why the objective of diagnosing the soil quality and propose technology for the recovery of these soils, under the experimental design technique, three pilot plots were installed within the 3500 hectares that make up the San Simon sector where areas with the highest degree of degradation were selected, The remediation technologies seek to restore the natural properties of the soil, since it provides ecosystemic services such as water regulation, water capture and storage, and the conservation of the soil's natural properties: water regulation, carbon sequestration, soil protection and biodiversity conservation; if this resource is affected it brings with it a series of causes such as water scarcity, food and nutritional insecurity, accelerates climate change and reduces ecosystem services. For this purpose, the physicochemical analysis of specific soil parameters such as pH, humidity, organic matter, apparent and real density, arsenic and granulometric composition was carried out, thus determining the variables that prevent or complicate the regeneration of the vegetation cover and propose the appropriate remediation technology after the analysis and interpretation of the data obtained, concluding with a mixture of additives in different percentages applied in each plot in order to mitigate the degradation of these soils and recover them.